Aktivitas Pengungkapan Diri Remaja Putri Melalui Sosial Media Twitter - Ria Yunita (Jurnal Komunikasi, 2019)
Abstract -The phenomenon of self-disclosure, which is carried out by young women through Twitter is something interesting to study. Twitter becomes an online diary for most users, the term used in microblogs "what are you doing" where twitter users can write their activities, free twitter users reveal anything either just tell what is being done, the purpose of the study to find out self-disclosure young women through twitter social media in Jakarta through the role of Twitter, both in the form of reasons, traits, topics, and values in doing so. The theory used is Adolescent Development Psychology, Self Disclousure theory, and CMC (Computer Mediated Communication). This study uses qualitative methods that are descriptive and with a discourse analysis approach, namely data collected in the form of words and images. The technique of collecting data was in-depth interviews with 3 selected informants. The results of the study are Twitter as a channel for the activities of young women who do self disclosure on Twitter to meet the needs of establishing friendships, especially old friendships and self-actualization. Conclusion, young women (research informants) feel comfortable doing self-disclosure on Twitter, self-disclosure such as status updates in the form of tweets for teenagers are considered more effective to express themselves than tell directly to certain people Keywords: Activity ,Selfdisclosure  Girl ,Twitter